Correlates of active commuting, transport physical activity, and light rail use in a university setting. (March 2021) - Crist, Katie; Brondeel, Ruben; Tuz-Zahra, Fatima; Reuter, Chase; Sallis, James F.; Pratt, Michael; Schipperijn, Jasper
Abstract: Introduction: This study identified correlates of active commute mode, transport physical activity (TPA), and intention to use light rail transit (LRT) at a large university in advance of a new LRT connection to campus. Methods: Staff, faculty and students completed a campus-wide travel survey in 2017. Multivariable logistic and linear regression models assessed associations between individual, organizational and environmental correlates with outcomes of interest in a sample of 6894 respondents to identify factors that may encourage a shift from vehicle to active commute modes and increase TPA. Results: Those who biked or walked to campus exceeded weekly physical activity recommendations in TPA alone. Commuting by transit was associated with higher levels of TPA, compared to vehicle commuting. Greater commute mode enjoyment was associated with active modes. Staff were least likely to commute via active transport (AT) and had fewer minutes of TPA. Women and Asian racial groups were less likely to report TPA. Rideshare and discounted transit pass use were positively associated with all outcomes. Conclusions: New LRT presents a critical opportunity to achieve gains in both campus health and environmental sustainability. The factors identified in this study should be further explored as potential intervention or programmatic targets to encourage mode shift. Highlights: Studied factors associated with travel mode and health in a large, diverse sample. Active commuters exceeded weekly physical activity guidelines. Transit commuters had higher physical activity than drivers. Active transport programs for women and minorities may be warranted. Identified organizational factors that could encourage active commuting.